2018
DOI: 10.1021/acs.jpcc.8b01661
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale Electronic Characterization of Defects in Silicon Carbide Nanowires by Electron Energy-Loss Spectroscopy

Abstract: The atomic-level resolution of scanning transmission electron microscopy (TEM) is used for structural characterization of nanomaterials, but the resolution afforded by TEM also enables electronic characterization of defects in these materials through electron energy-loss spectroscopy (EELS). Here, the power of EELS is harnessed to characterize the local band gap of inclusion defects in hexagonal silicon carbide nanowires with a high density of stacking faults. The band gaps we extract from the EELS data align … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Lately, more focus has been shifted to anion vacancies in high-temperature solid reactions. , Oxygen and/or halogen atom vacancies lead to a deviation from the stoichiometry to some degree. The defective center can be inferred through experimental measurements via, e.g., X-ray photoelectron spectroscopy (XPS), electron paramagnetic resonance (EPR), positron annihilation spectroscopy (PAS), and electron energy loss spectroscopy (EELS) via atomic-level resolution of transmission electron microscopy (TEM), but how can we assign these charge transitions and ascertain the defect levels that are responsible for the emission? Inspired by recent studies in semiconductors, computational studies in combination with experimental efforts can yield insightful and quantitative details about the impact of point defects. ,, The defect-induced electronic states and broad emission bands as a result of different chemical bonding environments in the ground and excited states can also be undertaken using this approach …”
Section: Introductionmentioning
confidence: 99%
“…Lately, more focus has been shifted to anion vacancies in high-temperature solid reactions. , Oxygen and/or halogen atom vacancies lead to a deviation from the stoichiometry to some degree. The defective center can be inferred through experimental measurements via, e.g., X-ray photoelectron spectroscopy (XPS), electron paramagnetic resonance (EPR), positron annihilation spectroscopy (PAS), and electron energy loss spectroscopy (EELS) via atomic-level resolution of transmission electron microscopy (TEM), but how can we assign these charge transitions and ascertain the defect levels that are responsible for the emission? Inspired by recent studies in semiconductors, computational studies in combination with experimental efforts can yield insightful and quantitative details about the impact of point defects. ,, The defect-induced electronic states and broad emission bands as a result of different chemical bonding environments in the ground and excited states can also be undertaken using this approach …”
Section: Introductionmentioning
confidence: 99%
“…In fact, a similar band gap has been recorded in defective 2H-SiC nanowires very recently. 28 Another remarkable feature is the relatively sharp tip of the CBM curve in 9R-SiC which indicates a smaller effective electron mass. 15R-SiC is already known to have a higher electron mobility than most SiC polytypes, 29 and therefore 9R-SiC is expected to be even more attractive for device applications.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The resulting value (∼3.4 eV) is clearly higher than that of 2H-SiC and is similar to that of GaN, suggesting that 9R-SiC would be a good candidate for high-frequency applications. In fact, a similar band gap has been recorded in defective 2H-SiC nanowires very recently . Another remarkable feature is the relatively sharp tip of the CBM curve in 9R-SiC which indicates a smaller effective electron mass.…”
Section: Resultsmentioning
confidence: 99%
“…It is shown that the adjacent stacking faults do not affect the bandgap of the wurtzite regions. For the zinc-blende parts, in contrast, the bandgap is influenced by the thickness of the segments [164].…”
Section: Physical Propertiesmentioning
confidence: 98%